1984
DOI: 10.1007/bf00982922
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine long-chain acyltransferase and oxidation of palmitate, palmitoyl coenzyme A and palmitoylcarnitine by pea mitochondria preparations

Abstract: Palmitoylcarnitine was oxidised by pea mitochondria.L-carnitine was an essential addition for the oxidation of palmitate or palmitoylCoA. When palmitate was sole substrate, ATP and Mg(2+) were also essential additives for maximum oxidation. Additions of CoA inhibited the oxidation of palmitate. It was shown that CoA was acting as a competitive inhibitor of the carnitine-stimulated O2 uptake. It is suggested that palmitoylacarnitine and carnitine passed through the mitochondrial barrier with ease but palmitoylC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…The activities of the ,-oxidation enzymes were approximately equally distributed in both organellar fractions (Table I). This result is in marked contrast to reports from other workers on the localization of the $-oxidation enzymes in higher plant cells (6,12,15,27), but is consistent with previous publications from this laboratory (21,30,32,34,35). It has been noted that the substrates of the ,8-oxidation enzymes do not easily cross the intact mitochondrial inner membrane, thus this membrane must be disrupted before detecting enzyme activity (34).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The activities of the ,-oxidation enzymes were approximately equally distributed in both organellar fractions (Table I). This result is in marked contrast to reports from other workers on the localization of the $-oxidation enzymes in higher plant cells (6,12,15,27), but is consistent with previous publications from this laboratory (21,30,32,34,35). It has been noted that the substrates of the ,8-oxidation enzymes do not easily cross the intact mitochondrial inner membrane, thus this membrane must be disrupted before detecting enzyme activity (34).…”
Section: Resultssupporting
confidence: 89%
“…Thomas and associates (21,30,35) reported that mitochondria from germinating pea seedlings were capable of the foxidation of fatty acids, and that this process was absolutely dependent upon added carnitine. Carnitine dependence is one Octenoyl-CoA was prepared by the mixed anhydride method as described by Miernyk and Trelease (24).…”
mentioning
confidence: 99%
“…Mammalian mitochondria also carry out the oxidation of fatty acids and are thought to contain separate pools of CoA for Krebs cycle activity and fl-oxidation (22). The ability of plant mitochondria to oxidize fatty acids is controversial (26) and may be tissue specific; however, they do contain carnitine: acetyltransferase activity (5, 23, and this report). The role of carnitine and carnitine:acetyltransferase in modulating acetylCoA inhibition in vivo remains to be elucidated.…”
Section: Resultsmentioning
confidence: 95%
“…In the simplest case of unsaturated fatty acids this is represented by a carboxyl group; in LPC, PAF, and AC it is a more elaborate structure exhibiting negative and positive charges contributed by phosphate or carboxyl and trimethylamine groups, respectively. The physiological function of AC is the transfer of fatty acids through the inner mitochondrial membranes, which probably involves a translocating protein (24). EB is a cyclic hexapeptide antibiotic with a stearic acid side chain, derived from various species ofAspergillus (1 1).…”
Section: Resultsmentioning
confidence: 99%